Older persons experiences of healthcare in rural Burkina Faso: Results of a cross sectional household survey - Ellen M. Goldberg; Mamadou Bountogo; Guy Harling; Till Baernighausen; Justine I. Davies; Lisa R. Hirschhorn (Public Library of Science (PLoS), 2022)
Ensuring responsive healthcare which meets patient expectations and generates trust is important to increase rates of access and retention. This need is important for aging populations where non-communicable diseases (NCDs) are a growing cause of morbidity and mortality. We performed a cross-sectional household survey including socio-demographic; morbidities; and patient-reported health system utilization, responsiveness, and quality outcomes in individuals 40 and older in northwestern Burkina Faso. We describe results and use exploratory factor analysis to derive a contextually appropriate grouping of health system responsiveness (HSR) variables. We used linear or logistic regression to explore associations between socio-demographics, morbidities, and the grouped-variable, then between these variables and health system quality outcomes. Of 2,639 eligible respondents, 26.8% had least one NCD, 56.3% were frail or pre-frail and 23.9% had a recent healthcare visit, including only 1/3 of those with an NCD. Highest ratings of care experience (excellent/very good) included ease of following instructions (86.1%) and trust in provider skills (81.1%). The HSR grouping with the greatest factor loading included involvement in decision-making, clarity in communication, trust in the provider, and confidence in providers' skills, labelled Shared Understanding and Decision Making (SUDM). In multivariable analysis, higher quality of life (OR 1.02,95%CI 1.01-1.04), frailty (OR 1.47,95%CI 1.00-2.16), and SUDM (OR 1.06,95%CI 1.05-1.09) were associated with greater health system trust and confidence. SUDM was associated with overall positive assessment of the healthcare system (OR 1.02,95%CI 1.01-1.03) and met healthcare needs (OR 1.09,95%CI 1.08-1.11). Younger age and highest wealth quintile were also associated with higher met needs. Recent healthcare access was low for people with existing NCDs, and SUDM was the most consistent factor associated with higher health system quality outcomes. Results highlight the need to increase continuity of care for aging populations with NCDs and explore strengthening SUDM to achieve this goal.